2019
DOI: 10.1002/ece3.5720
|View full text |Cite
|
Sign up to set email alerts
|

Ocean acidification during prefertilization chemical communication affects sperm success

Abstract: Ocean acidification (OA) poses a major threat to marine organisms, particularly during reproduction when externally shed gametes are vulnerable to changes in seawater pH. Accordingly, several studies on OA have focused on how changes in seawater pH influence sperm behavior and/or rates of in vitro fertilization. By contrast, few studies have examined how pH influences prefertilization gamete interactions, which are crucial during natural spawning events in most externally fertilizing taxa. One mechanism of gam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 53 publications
0
12
1
Order By: Relevance
“…Spawning was induced by placing mussels in a heated water bath (28°C), as is standard for M. galloprovincialis ( [36], e.g. [49,50]).…”
Section: Methods (A) Mussel Collection and Spawningmentioning
confidence: 99%
See 1 more Smart Citation
“…Spawning was induced by placing mussels in a heated water bath (28°C), as is standard for M. galloprovincialis ( [36], e.g. [49,50]).…”
Section: Methods (A) Mussel Collection and Spawningmentioning
confidence: 99%
“…These factors, as well as the tractability of M. galloprovincialis for spawning and gamete manipulation experiments (e.g. [35,36]), make it an excellent model system for exploring the effects of ocean warming on sperm. A previous study found that sperm of M. galloprovincialis appeared to maintain normal swimming behaviour and fertilization competence under short-term exposure to high temperatures [37], although decreased fertilization rates have also been reported at elevated temperatures [35].…”
Section: Introductionmentioning
confidence: 99%
“…This could be an important bottleneck for population fitness, as sperm activation and motility are vital for fertilization across metazoan phyla. Importantly, the response of sperm to ocean acidification is nuanced, as both positive and negative shifts in sperm performance have been observed at the level of the individual male in molluscs and echinoderms ( 77 80 ). This phenotypic diversity highlights the need to better understand the fundamental mechanisms that regulate sperm performance in order to predict how the fitness of corals and other marine invertebrates will be affected by a changing marine environment.…”
Section: Discussionmentioning
confidence: 99%
“…This could be an important bottleneck for population fitness, as sperm activation and motility are vital for fertilization across metazoan phyla. Importantly, the response of sperm to ocean acidification is nuanced, as both positive and negative shifts in sperm performance have been observed at the level of the individual male in molluscs and echinoderms (70)(71)(72)(73). This phenotypic diversity highlights the need to better understand the fundamental mechanisms that regulate sperm performance in order to predict how the fitness of corals and other marine invertebrates will be affected by a changing marine environment.…”
Section: Discussionmentioning
confidence: 99%